Metal lithium-lithium-rich manganese-based battery and preparation method thereof
By using lithium-rich manganese-based material positive electrode and lithium negative electrode in metal lithium batteries and forming a protective film on the surface of the negative electrode, the lithium dendrites problem is solved, and the battery performance with high energy density and long cycle life is achieved.
Patent Information
- Application Number
- CN202510316264.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-07-11
AI Technical Summary
The poor electrochemical reversibility of metal lithium negative electrodes, the problems of dendrite generation and dead lithium formation restrict the practicalization of lithium metal secondary battery technology.
Lithium-rich manganese-based material is used as the positive electrode and metal lithium is used as the negative electrode, and the protective film is formed by in-situ polymerization of electrolyte on the surface of the negative electrode, and the separator is coated with a solid electrolyte to avoid the damage of lithium dendrites.
The long cycle life of high-energy density batteries is achieved, the formation of lithium dendrites is reduced, and the circulation performance is improved.
Smart Images

Figure CN120300260A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and particularly relates to a lithium metal-lithium-rich manganese-based battery and a preparation method thereof. Background Art
[0002] In recent years, new system battery technologies such as solid-state batteries, lithium-sulfur batteries, and metal-air batteries have continuously made breakthroughs, and the specific energy has reached more than 400 Wh / kg. In order to make the new system batteries practical, the specific energy of a single battery cell needs to reach more than 500 Wh / kg. For the realization of the target energy density of 500 Wh / kg, from the current technology perspective, battery systems with high-voltage range, high specific capacity cathode materials, and lithium metal anode materials have become an inevitable choice.
[0003] However, problems such as the inherently poor electrochemical reversibility of lithium metal anodes, dendrite generation, and dead lithium formation have always been the key bottlenecks restricting the practical application of lithium metal secondary battery technologies.
[0004] Therefore, providing a lithium secondary battery with high energy density and good cycling performance is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0005] In view of the problems such as the inherently poor electrochemical reversibility of lithium metal anodes, dendrite generation, and dead lithium formation, the present invention proposes a lithium metal-lithium-rich manganese-based battery and a preparation method thereof. By using a lithium-rich manganese-based material for the positive electrode, lithium metal for the negative electrode, solidifying the electrolyte into a film on the surface of the negative electrode, and using a solid electrolyte to coat the separator, the destruction of lithium dendrites is avoided, and a long cycle life of a high-energy density battery is achieved.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A lithium metal-lithium-rich manganese-based battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator;
[0008] Wherein, the active material of the positive electrode sheet is a lithium-rich manganese-based material:
[0009] The negative electrode includes a copper layer, lithium layers covering both sides of the copper layer, and a protective film covering the lithium layers;
[0010] The preparation method of the protective film is to form it by in-situ polymerization of a polymerization monomer and an initiator in the electrolyte on the surface of the lithium layer.
[0011] Preferably, the polymerization monomer includes at least one of pentaerythritol tetraacrylate, methoxypolyethylene glycol acrylate, ethoxylated trimethylolpropane triacrylate, polyethylene glycol diacrylate, and dipropylene glycol diacrylate;
[0012] The initiator is azobisisobutyronitrile.
[0013] Preferably, the mass ratio of the polymerization monomer to the initiator is 10 - 25:1;
[0014] The addition amount of the polymerization monomer is 3 - 10% of the electrolyte injection amount.
[0015] Preferably, the conditions for in-situ polymerization are to react for 1 - 4 h in an environment of 50 - 100 °C.
[0016] Preferably, the thickness of the copper layer is 4 - 8 μm, the single-layer thickness of the lithium layer is 5 - 60 μm, and the thickness of the protective film is 1 - 3 μm.
[0017] Preferably, the electrolyte further includes an ester organic solvent and a lithium salt electrolyte;
[0018] Among them, the ester organic solvent includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl acetate, ethyl acetate, propyl acetate, and propyl propionate; the mass percentage of the ester organic solvent in the electrolyte is 0 - 95%;
[0019] The lithium salt electrolyte includes at least one of lithium hexafluorophosphate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalate borate, lithium bis(oxalato)borate, and lithium tetrafluoroborate; the concentration range of the lithium salt electrolyte is 1 - 5 mol / L.
[0020] Preferably, the single-layer thickness of the active material of the positive electrode sheet is 18.5 - 92.6 μm;
[0021] The active material layer includes the following raw materials by mass percentage: 90 - 97% of lithium-rich manganese-based material, 0 - 3.5% of carbon nanotubes, 0 - 3% of conductive carbon black, and 1 - 3.5% of polyvinylidene fluoride.
[0022] Preferably, the preparation method of the active material layer is as follows:
[0023] Weigh the raw materials according to the mass percentage, add the raw materials into NMP solvent and mix evenly to obtain a positive electrode slurry with a solid content of 50 - 70%; coat the positive electrode slurry on both sides of the surface of the positive electrode current collector, and the dried coating is the active material layer.
[0024] Preferably, the thickness of the positive current collector is 12 μm, and the total thickness of the positive electrode sheet is 49 - 197 μm.
[0025] Preferably, the structure of the separator is a base film and LATP coatings covering the upper and lower surfaces of the base film;
[0026] The thickness of the base film is 6 - 12 μm, and the single-sided thickness of the LATP coating is 1 - 3 μm.
[0027] Preferably, the base film is polyethylene (PE).
[0028] According to the above-mentioned preparation method of a lithium metal - lithium-rich manganese-based battery, it includes the following steps:
[0029] (1) Prepare the positive electrode sheet, negative electrode sheet and separator, and configure the electrolyte for standby according to the raw materials of the electrolyte;
[0030] (2) After drying the positive electrode sheet, negative electrode sheet and separator, stack them in the order of the positive electrode sheet, the separator and the negative electrode sheet, then assemble the battery core, assemble it into a soft-pack battery, then dry the battery core and inject the electrolyte, and place the battery after injecting the electrolyte in an environment of 50 - 100 °C for 1 - 4 h to solidify the film, and finally obtain a lithium metal - lithium-rich manganese-based battery through formation, encapsulation and grading.
[0031] Preferably, the injection of the electrolyte and the mixing of the positive electrode paste are required to be carried out in an environment with a dew point of -40 °C.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] The lithium metal - lithium-rich manganese-based battery provided by the present invention solidifies the film on the surface of the negative electrode through the electrolyte and uses a solid electrolyte to coat the separator, reducing the formation of lithium dendrites and the impact on the battery cycle performance, and realizing the long cycle life of a high-energy density battery. Description of the Drawings
[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required to be used in the description of the embodiments or the prior art. The drawings in this description are only the embodiments of the present invention.
[0035] Figure 1 It is a schematic diagram of the battery structure of Embodiment 1 of the present invention;
[0036] Figure 2 It is a schematic diagram of the separator structure of Embodiment 1 of the present invention;
[0037] Figure 3 It is a schematic diagram of the negative electrode structure of Embodiment 1 of the present invention;
[0038] Figure 4 It is a graph of the battery cycle test results of Embodiment 1 of the present invention. Detailed Embodiments
[0039] Embodiments of the present invention are described below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described with reference to the accompanying drawings are exemplary and are intended to explain the present invention, rather than being construed as a limitation on the present invention.
[0040] Embodiment 1
[0041] The present invention provides a method for preparing a lithium metal-lithium-rich manganese-based battery, comprising the following steps:
[0042] (1) Prepare the positive electrode sheet: Weigh the following raw materials by mass percentage, 96.7% of lithium-rich manganese-based material (Beijing Chuangneng Huitong Technology Co., Ltd., model HP-C01), 0.5% of carbon nanotubes, 1.5% of conductive carbon black, and 1.3% of PVDF; mix the lithium-rich manganese-based material, carbon nanotubes, conductive carbon black, and PVDF evenly in NMP solvent to obtain a positive electrode slurry with a solid content of 65%; double-sidedly coat the positive electrode slurry on the surface of a 12-μm positive electrode current collector, dry and die-cut to obtain a positive electrode sheet with a positive electrode active material layer thickness of 120 μm, and set aside;
[0043] Prepare the negative electrode sheet: Double-sidedly coat a lithium layer 1-2 (the thickness of the lithium layer is 15 μm) on a 6-μm copper layer 1-1, and obtain a negative electrode sheet after trimming and slicing, and set aside;
[0044] Prepare the separator: Double-sidedly coat a 3-μm LATP coating 2-2 on a 6-μm polyethylene-based film 2-1, and obtain a separator after trimming, slicing, and drying (the structure is as Figure 2 ), and set aside;
[0045] Prepare the electrolyte: Mix 5% of ethoxylated trimethylolpropane triacrylate (ETPTA), 5% of dipropylene glycol diacrylate (TPGDA), and 1% of azobisisobutyronitrile (AIBN) evenly, and set aside. 5% and 1% refer to 5% and 1% of the conventional electrolyte injection volume; the components of the conventional electrolyte are shown in Table 1 below:
[0046] Table 1 Components of the conventional electrolyte
[0047] Reagent Abbreviation Reagent Name Mass Ratio TMSP Trimethylsilyl Phosphate 0.50% LiP02F2 Lithium Difluorophosphate 5.00% EMC Ethyl Methyl Carbonate 7.50% DEC Dimethyl Carbonate 42.20% VC Vinylene Carbonate 0.50% FEC Fluoroethylene Carbonate 2.50% DTD Ethylene Sulfate 21.10% EC Ethylene Carbonate 0.50% PS 1,3 - Propane sultone 2.50% PST 1 - Propene - 1,3 - sultone 0.50% LiODFB Lithium difluoro(oxalato)borate 1.00% LiBF4 Lithium Tetrafluoroborate 0.20% LiPF6 Lithium Hexafluorophosphate 16.00%
[0048] (2) Stack the positive electrode sheet 1, separator 2, and negative electrode sheet 3 in sequence and then assemble the battery cell (the structure is as Figure 1 ), assemble into a soft-pack pouch-type battery, then dry the battery cell and inject the electrolyte. After injecting the electrolyte, place the battery in an environment of 80 °C for 1 h to cure and form a film, and a 1-3-μm protective film 1-3 is formed on the surface of the negative electrode (the structure is as Figure 3) Finally, through formation, encapsulation, and formation and grading, a lithium metal-lithium-rich manganese-based battery is obtained. Among them, the conditions for formation are: formation temperature of 85 °C, formation pressure of 15 MPa; the formation procedure is constant current charging at 0.01C for 60 min, constant current charging at 0.05C for 240 min, constant current charging at 0.1C for 240 min, constant current charging at 0.2C for 240 min, and a cut-off voltage of 4.25V.
[0049] The performance of the lithium metal battery (13Ah soft-pack battery) in Example 1 was tested. The charge and discharge rate was 0.1C / 0.1C, 0.1C / 0.2C, 0.1C / 0.5C, and the charge and discharge voltage range was 2.5 - 4.4V. The results are shown in Table 2 and Figure 4 as follows.
[0050] Table 2 Test results of the performance of the lithium metal battery in Example 1
[0051]
[0052] As can be seen from Table 1, for the lithium metal battery of the present invention, by using a lithium-rich manganese material with a high specific capacity and a lithium metal negative electrode, the energy density reaches more than 500 Wh / kg. By solidifying a film on the surface of the negative electrode with the electrolyte, the influence of lithium dendrites on the cycle performance of the battery is mitigated, enabling the battery life to reach 200 cycles and the capacity retention rate to be higher than 80%.
[0053] Comparative Example 1
[0054] Using a lithium-rich manganese material and a high-nickel ternary material as the positive electrode respectively, and paired with a lithium metal as the negative electrode, soft-pack batteries of the same model were made. The battery capacity and energy density are shown in Table 3 below. At the same voltage, the energy density of the lithium-rich manganese-based battery is significantly higher than that of the high-nickel ternary battery.
[0055] Table 3 Results of the battery capacity and energy density of the soft-pack battery in Comparative Example 1
[0056]
[0057] Comparative Example 2
[0058] Two in-situ polymerization electrolytes and a conventional electrolyte were respectively injected into a soft-pack battery with a capacity of 4100 mAh. The positive electrode active material of this battery is a 1:1 mixture of medium-high nickel ternary and lithium cobaltate, and the negative electrode active material is artificial graphite;
[0059] Among them, the formulation of in-situ polymerization electrolyte 1 is 5% ethoxylated trimethylolpropane triacrylate (ETPTA) + 5% dipropylene glycol diacrylate (TPGDA) + 1% azobisisobutyronitrile (AIBN) mixed evenly + conventional electrolyte. The formulation of in-situ polymerization electrolyte 2 is 5% PETEA + 1% azobisisobutyronitrile (AIBN) mixed evenly + conventional electrolyte. The remaining preparation steps and parameters are the same as those in Example 1.
[0060] The 25°C rate discharge performance, energy density, and nail penetration performance of the battery are tested as shown in Tables 4 - 6 below. It can be seen that by using the in-situ polymerization electrolyte, a film can be cured on the surface of the negative electrode and a solid electrolyte can be used to coat the separator, reducing the formation of lithium dendrites and their impact on the battery cycle performance, and achieving a long cycle life for high-energy density batteries.
[0061] Table 4 Results of 25°C rate discharge performance
[0062] Model 0.2C Capacity mAh 0.5C Capacity mAh 0.5C Capacity Retention Rate 1C Capacity mAh 1C Capacity Retention Rate In - situ Polymerized Electrolyte 1 4192 4105 97.92% 3988 95.13% In - situ Polymerized Electrolyte 2 4163 4057 97.45% 3899 93.66% Conventional Electrolyte 4251 4182 98.38% 4141 97.41%
[0063] Table 5 Battery energy density results
[0064]
[0065] Table 6 Results of nail penetration performance test
[0066]
[0067] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that: they can still modify the technical solutions recorded in the foregoing embodiments, or perform equivalent replacements on some of the technical features; and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lithium metal-lithium-rich manganese-based battery, characterized in that, It includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator; Among them, the active material of the positive electrode sheet is a lithium-rich manganese-based material: The negative electrode includes a copper layer, lithium layers covering both sides of the copper layer, and a protective film covering the lithium layers; The preparation method of the protective film is to in-situ polymerize the polymerization monomer and initiator in the electrolyte on the surface of the lithium layer.
2. The lithium metal-lithium-rich manganese-based battery according to claim 1, wherein The polymerization monomer includes at least one of pentaerythritol tetraacrylate, methoxypolyethylene glycol acrylate, ethoxylated trimethylolpropane triacrylate, polyethylene glycol diacrylate, and dipropylene glycol diacrylate; The initiator is azobisisobutyronitrile.
3. The metal lithium-lithium rich manganese based battery according to claim 1, characterized in that, The mass ratio of the polymerization monomer to the initiator is 10 - 25:1; The addition amount of the polymerization monomer is 3 - 10% of the electrolyte injection volume.
4. The lithium metal-lithium-rich manganese-based battery according to claim 1, wherein, The conditions for the in-situ polymerization are to react for 1 - 4 h in an environment of 50 - 100 °C.
5. The metal lithium-lithium-rich manganese-based battery according to claim 1, characterized in that, The thickness of the copper layer is 4 - 8 μm, the single-layer thickness of the lithium layer is 5 - 60 μm, and the thickness of the protective film is 1 - 3 μm.
6. The lithium metal-lithium-rich manganese-based battery according to claim 1, wherein The electrolyte further includes an ester organic solvent and a lithium salt electrolyte; Among them, the ester organic solvent includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl acetate, ethyl acetate, propyl acetate, and propyl propionate; the mass percentage of the ester organic solvent in the electrolyte is 0 - 95%; The lithium salt electrolyte includes at least one of lithium hexafluorophosphate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalate borate, lithium bis(oxalate)borate, and lithium tetrafluoroborate; the concentration range of the lithium salt electrolyte is 1 - 5 mol / L.
7. The lithium metal-lithium-rich manganese-based battery according to claim 1, characterized in that, The single-layer thickness of the active material of the positive electrode sheet is 18.5 - 92.6 μm; The active material layer includes the following raw materials by mass percentage: 90 - 97% of lithium-rich manganese-based material, 0 - 3.5% of carbon nanotubes, 0 - 3% of conductive carbon black, and 1 - 3.5% of polyvinylidene fluoride.
8. The lithium metal-lithium-rich manganese-based battery according to claim 7, characterized in that The preparation method of the active material layer is as follows: Weigh the raw materials according to the mass percentage, add the raw materials to NMP solvent and mix them evenly to obtain a positive electrode slurry with a solid content of 50 - 70%; double-sided coat the positive electrode slurry on the surface of the positive electrode current collector, and the coating after drying is the active material layer.
9. The metal lithium-lithium-rich manganese-based battery according to claim 1, characterized in that, The structure of the separator is a base film and LATP coatings covering the upper and lower surfaces of the base film; The thickness of the base film is 6 - 12 μm, and the single-sided thickness of the LATP coating is 1 - 3 μm.
10. The preparation method of a lithium metal-lithium-rich manganese-based battery according to any one of claims 1-9, characterized in that, It includes the following steps: (1) Prepare the positive electrode sheet, negative electrode sheet, and separator, and prepare the electrolyte in advance according to the raw materials of the electrolyte; (2) After drying the positive electrode sheet, negative electrode sheet, and separator, stack them in the order of the positive electrode sheet, the separator, and the negative electrode sheet for cell assembly to form a soft-pack battery. Then, after cell drying and electrolyte injection, place the battery after electrolyte injection in an environment of 50 - 100 °C for 1 - 4 h to cure and form a film. Finally, through formation, encapsulation, and grading, a lithium metal-lithium-rich manganese-based battery is obtained.